Social Business and Entrepreneurship Development: A Critical Analysis - Salim Bhuyan, Mohammed; Raju, Valliappan; Poh Phung, Siew (International Journal of Psychosocial Rehabilitation, 2019)
Social business is visionary new dimension for capitalism. It is invented by Nobel Laureate Professor Dr. Muhammad Yunus. Social business targets business opportunities which are neglected by conventional profit maximizing companies. In social business profits are not rewarded shareholders but in extending the ambition of the business. Entrepreneurship is a process of starting new business. The process by which an entrepreneur is created is also called entrepreneurship. The people who do so are called 'entrepreneurs'. Entrepreneur is a person who states, organize and many any enterprise specially a business usually considerable initiatives and risks. Entrepreneur works differently from an employee. An entrepreneur runs his business or enterprise and responsible for all the risks and rewards of that given business or enterprise. Entrepreneur is the business leader and innovator. There are some differences between social business and entrepreneurship development.